Política de educação profissional e tecnológica: avaliação das contribuições do IFCE para o desenvolvimento dos Sertões de Crateús-CE - Gomes, Antonia Karla Bezerra (2020)
In Brazil, starting in the 2000s, the public policy of Professional and Technological Education (abbreviated to EPT in Portuguese) was structured in new paradigms, emphasized on the expansion and internalization in order to democratize access and, above all, the establishment of a dialogue with local productive arrangements, in order to reduce inequalities through one regional development driven by teaching and research applied to the needs of the inhabitants. Considering such an expectation, this work consists in one research an evaluation of the Professional and Technological Education Policy of the Federal Education Network, having as a case study the Federal Institute of Ceará (IFCE in Portuguese), and more specifically its performance in the Country Areas in the Region of Crateús, CE. The main question in this evaluation is to know to what ways the technology and professional education in your three axes (teaching, research and extension), has contributed to citizen formation and to local and regional socioeconomic development. The methodology of this investigation used the four dimensions of “in-depth assessment” (RODRIGUES, 2008), which are: (I) context analysis; (II) content analysis; (III) institutional trajectory analysis; and (IV) temporal-territorial spectrum analysis. In function of your regional importance and, also for the data and information availability, the evaluation spatially circumscribed the city of Crateús, regional pole. The research results point the Campus of Crateús, despite the short time of operation, less than a decade, has already managed to influence local and regional socioeconomic development in educational aspects- professionalization, cultural- behavior change and new values incorporation, social- access to the right to education and other services offered by the Campus, and economic- from the inputs generated by the fixed operation, through its final action of teaching, research and extension. Its biggest challenge concerns maintaining a solid and permanent dialogue with the community to build a consolidated sustainable development project